2017
DOI: 10.1109/jstars.2017.2679159
|View full text |Cite
|
Sign up to set email alerts
|

Downstream Services for Rice Crop Monitoring in Europe: From Regional to Local Scale

Abstract: The ERMES agro-monitoring system for rice cultivations integrates EO data at different resolutions, crop models and user-provided in-situ data in a unified system which drives two operational downstream services for rice monitoring. The first is aimed at providing information concerning the behaviour of the current season at regional/rice district scale, while the second is dedicated to provide farmers with field-scale data useful to support more efficient and environmentally-friendly crop practices. In this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…Besides their usefulness as input for monitoring systems devoted to assess crop condition, these products can be also of value as inputs for crop modelling studies. This have been already demonstrated during the pre-operational activities of the ERMES project, where low-resolution data derived by aggregating the GEOV1 on a 2 km × 2 km regular grid were assimilated in the Water Accounting Rice Model (WARM) crop model to provide seasonal estimates of rice yield at district scale [12,70]. In these studies, it was found that regional yield estimation benefits from exogenous LAI inclusion in crop modelling.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Besides their usefulness as input for monitoring systems devoted to assess crop condition, these products can be also of value as inputs for crop modelling studies. This have been already demonstrated during the pre-operational activities of the ERMES project, where low-resolution data derived by aggregating the GEOV1 on a 2 km × 2 km regular grid were assimilated in the Water Accounting Rice Model (WARM) crop model to provide seasonal estimates of rice yield at district scale [12,70]. In these studies, it was found that regional yield estimation benefits from exogenous LAI inclusion in crop modelling.…”
Section: Discussionmentioning
confidence: 84%
“…Besides for "direct" mapping studies, these products can be also of value as inputs for crop modelling studies. This have been already demonstrated during the pre-operational activities of the ERMES project, where low-resolution data derived by aggregating the GEOV1 on a 2 km × 2 km regular grid were assimilated in the Water Accounting Rice Model (WARM) crop model to provide seasonal estimates of rice yield at district scale [12,69]. The EPS LAI maps share the same possible problem of representing an effective LAI value illustrated above for HR products.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations